High-Level Mobility Assessment Tool Normative Values for Children. Issue 2 (19th November 2019) - Eldridge, Beverly J; Galea, Mary P; Kissane, Anne L; Broder, Jonathan C; Brilleman, Samuel L; Wolfe, Rory; Williams, Gavin
Abstract: Background: Physical therapists need to be able to evaluate high-level gross motor skills of children to determine their capacity to engage in activities such as running, jumping, hopping, and stair climbing. The High-Level Mobility Assessment Tool (HiMAT) has excellent interrater and retest reliability and is less susceptible to a ceiling effect than existing mobility scales in children who are 6 to 17 years old and have traumatic brain injury. Objective: The purposes of this study were to develop normative HiMAT score ranges for Australian children and to investigate the relationship between children's HiMAT scores and their age, height, weight, and body mass index (BMI). Design: This study used a cross-sectional design. Methods: Children included in this study were 5 to 12 years old, had no condition affecting their mobility, could follow 2-stage instructions, and had written informed consent from their parent or guardian. A total 1091 children were assessed at their local school, where their height, weight, and HiMAT score were recorded. The relationships between children's age, height, weight, and BMI were summarized using Spearman rank correlations. Truncated regression models were used to determine the most appropriate predictor variable for developing sex-specific normative ranges. Results: There was a positive correlation between children's HiMAT scores and their age, height, weight, and BMI. Age explained the most variability in HiMAT scores for both boys and girls. Limitations: The reliability, validity, and responsiveness of the HiMAT have not been tested across a broad range of children with mobility limitations. Normative data reported in this study are for Australian children only. Conclusions: HiMAT scores for children in this study increased with age, height, weight, and BMI. Age was the most appropriate variable for developing a normative dataset of HiMAT scores for children of primary school age.